Jaina System of Knowledge Management A Comparative Study with Modern Knowledge Management System - Jain, Dr Alka (IJRDO -Journal of Computer Science Engineering, 2015)
Modern definitions of data, information and knowledge explain them in these words, “ and Dataare unorganised and unprocessed fact.Information means shaping the data to arrive at a meaningin the eyes of the perceiver.Knowledge is human understanding of information based on itsperceived importance or relevance to a problem area.” The author was able to find a sililar pathof guidelines in Jaina Knowledge Management system and modern management system. Originof Jaina KMS is at least 2500 years back while modern KMS is in its infancy stage yet. Acomparative analysis of top attributes of both the KMS – one ancient and one modern, has beendone in this study. Architecture in Jain literature and user Training in Jaina Agamic System hasbeen studied. In Jaina KMS निक्षेप, प्रमाण and ज्ञाि etc. are the tools to know anything.Jaincommunity has been treated as The Knowledge Organisation. Knowledge Creation andKnowledge Post system evaluation of the knowledge in Jainism is kaiwalya (Self realisationafter gaining all the knowledge). According to Awad and Ghaziri, Knowledge Managementsystem is developed to gather, organize, refine and distribute knowledge. This process takesplace in Jaina Knowledge Management System through ‘स्वाध्याय, वाचिा,पच्ृछिा,अिुप्रेक्षा, धममकथा etc. The comparison has been done by quoting modern management scholars and ancientJaina scriptures like Uttradhyayan Sutra and Nandi Sutra. All the members of Jain Communityhave been treated as members of an organisation.In fact the whole coomunity is treated as anorganisation.Then the theory of modern knowledge management system has been tested on Jaintreasure of knowledge to verify that a sound knowledge management system used to exist andstill exists in Jain community, which has helped in safety and security of the knowledge in itsdispersion to other followers